Brunona z Kwerfutu wyprawa do Pieczyngów – aspekty misyjne i polityczne - Paroń, Aleksander (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The Journey of Bruno of Querfurt to the Pechenegs – its Politics and Mission. The present study examines the reasons behind the journey by Bruno of Querfurt to the Pechenegs. According to the author, there is no indication that the missionary was involved in any political plans Boleslaw the Brave may have had for the steppe dwellers. The idea of the journey to the Pechenegs came from Bruno himself and was the most radical form of the missio ad gentes, for its object was meant to be “the cruellest people among pagans”. Bruno treated the mission to the land of the Pechenegs as an ardent confession of faith and spiritual trial.